Uncovering the determinants of low involvement of the elderly in chronic disease management: A qualitative approach at Ratih Clinic, Badung - Budiartami , Putu Paramitha; Ani, Luh Seri (Institute of Computer Science (IOCS), 2025)
The Chronic Disease Management Program (CDMP) aims to improve the quality of life of the elderly through the control of non-communicable diseases such as hypertension and diabetes. However, the participation of the elderly at the Tabanan Ratih Clinic is still low, hampering the effectiveness of the program. This study aims to identify the factors that play a role in the low involvement of the elderly in CDMP. Qualitative research with a descriptive phenomenological approach was conducted at the Ratih Clinic in Badung in March-June 2024. Data was collected through in-depth interviews with 10 elderly people (aged 60-70 years) who had low participation and 6 health workers. Thematic analysis is used to identify determinants. Four main themes were found, namely (1) accessibility and mobility barriers, (2) lack of knowledge and negative perception of CDMP, (3) lack of family and social support, and (4) economic factors and time priorities. The low participation of the elderly is influenced by interrelated multidimensional factors. Recommendations include the provision of free transportation, local culture-based education, family involvement, and the integration of CDMP with community activities such as the elderly Posyandu. These findings support the development of inclusive strategies to increase the involvement of the elderly in chronic disease management, in line with CDMP' goals.